Analisis Sistem Pengendalian Manajemen dalam Upaya Meningkatkan Daya Saing - Stephanie Natania; Rianti Simanjuntak; Fasiduhu Baene; Toman Sony Tambunan (Lembaga Pengembangan Kinerja Dosen, 2025)
The problem of this research is how the implementation of the management control system in TOSERBA MMTC and what strategies are carried out to improve competitiveness in TOSERBA MMTC. The purpose of this study is to determine how the implementation of the management control system in TOSERBA MMTC and to determine what strategies are carried out to improve competitiveness in TOSERBA MMTC. This research method uses a qualitative approach. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the study TOSERBA MMTC has implemented a structured management control system at three levels: strategic, operational, and financial. Strategic involves quarterly planning based on historical data; operational combines computerized information systems and a collaborative work culture; while finance applies tiered authorization and bottom-up budgeting, which has successfully reduced budget deviations by 22%. To improve competitiveness, MMTC carries a hyperlocal strategy by selling 45% local products, digital transformation such as WhatsApp Business and dynamic discount systems, and marketing through local social media and digital loyalty programs, which have proven effective in increasing sales and customer retention.